Measuring Airborne Particulate Concentrations in Two Wisconsin Towns Hosting Frac Sand Facilities - Pierce, Crispin; Kleist, Ben; Braunling, Ken; Fuhrman, Ethan; Kentnich, Jacob; Cowart, Maryanne; Husnik, Peter (My University, 2018)
Airborne particulates (dust) include the PM2.5 fraction and its larger counterpart, PM10, and are subject to National Ambient Air Quality Standards under the Clean Air Act. Health effects associated with chronic exposure to PM2.5 include cardiovascular issues and lung disease (including lung cancer). The proximity of these and mine facilities to population centers has raised concerns about human exposure to airborne pollutants, especially PM2.5 and respirable crystalline silica. The purpose of this study is to monitor airborne particulate concentrations to protect the public against related health effects.
Color poster with text, graphs, maps, and images.
Keywords: Sand mining; Frac sand; Airborne particulates; Air quality; Posters